IJCM_155A: Socio-demographic profile of patients with Dermatophytoses in tertiary care hospitals in Coastal South India - Joshi Anadhi; Mithra Prasanna; Unnikrishnan Bhaskaran; Rekha T; Kumar Nithin; Holla Ramesh; Nayak Kashinath; Mudaliyar Kavya V; Tripathi Kriti S; Kondeti Kritin; Dhakshinamoorthy Srinath (Wolters Kluwer Medknow Publications, 2024)
Background: Dermatophytoses or Dermatophytic infections are diseases characterized by the infection of keratinized tissues. This study was done to study the epidemiological profile and factors associated with Dermatophytosis and the awareness towards the same among patients with such infections. Methodology: This cross-sectional study was carried out in the tertiary hospitals affiliated with Kasturba Medical College, Mangalore. A semi-structured questionnaire was used for the collection of data, which was entered and analysed using SPSS version 25. The results were expressed as proportions. To compare the groups, the Chi-square test was used and p<0.05 was considered statistically significant. Results: Out of the total 118 patients who were included in the study, 57% (n=67) were males. The mean age of the participants was 33.93 years (S.D-12.76). According to our study, among the 118 participants studied, 31% (n=37) of the infected cases belonged to the low-income group (Upper lower), and 63% (n=74) of infected cases belonged to the middle-income group. The study population attributed the occurrence of dermatophytosis to poor skin hygiene (24.5%) followed by occupational exposure (20.1%). A higher proportion, 73% of the patients have increased exposure to water, soil/organic matter, or both. Overall, 90.6% (n=107) were unaware of the complications of the disease and 83.9% (n=99) patients didn't know of the safety practices followed to prevent it. Conclusion: The occurrence of dermatophytosis is the highest among middle and lower socioeconomic strata people. Poor hygiene, contact with patients and reduced immunity are important risk factors for the disease.